High Pre-treatment Neutrophil-to-Lymphocyte ratio (NLR) and Platelet-to-Lymphocyte ratio (PLR) Shows Lower Progressive-free Survival and Overall Survival in Tyrosine Kinase Inhibitor-treated Lung Adenocarcinoma - Kusumawardhani, Erna; Haryati, Haryati; Arganita, Fidya Rahmadhany (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: The role of Neutrophil-to-Lymphocyte ratio (NLR) and Platelet-to-Lymphocyte ratio (PLR) as an easy and inexpensive prognostic examination modality has different results. While the combination of the two has never been done.Objective: This study investigated the association between NLR/PLR and outcomes in advanced lung adenocarcinoma Epidermal Growth Factor Receptor (EGFR) mutation-positive with Tyrosine Kinase Inhibitor (TKI) treatment.Methods: This retrospective study enrolled 40 medical records of lung adenocarcinoma patients treated with TKI in Ulin General Hospital from 2017-2019, with follow-up until April 1, 2021. A receiver operating curve (ROC) was performed to determine the optimal cut-off and parallel tests of NLR/PLR combination. The Kaplan-Meier was used to evaluate the impact on progressive-free survival (PFS) and overall survival (OS).Results: The optimal cut-off was 6.25 for NLR and 451.5 for PLR with sensitivity and specificity of PFS (31.6%, 100%, and 18.4%, 100%) and OS (32.4%, 100% and 8.9%, 100%) (AUC 0.362, 0.329 and 0.482, 0.477) respectively. Patients in NLR <6.25 and PLR <451.5 groups presented longer PFS (10 months, 95% CI:7.783 -12.217, vs. 8 months, 2.908-13.092, p=0.821; 10 months, 7.508 – 12.492 vs. 9 months, 6.434-11.566, p=0.513) and OS (20 months, 14.017-25.983 vs.16 months, 11.474-20.526, p=0.378; 20 months, 14.629-25.371 vs. 14 months, 3.735-24.265, p=0.382) but not significantly correlated.Conclusion: High pre-treatment NLR and PLR showed shorter PFS and OS, although they did not appear as a prognostic marker for PFS and OS of EGFR-mutant lung adenocarcinoma treated with TKI.